Need Analysis for Developing STEM Integrated Electronic Teaching Material of Alternative Energy to Promote Students’ Creative Thinking Skills - lestari, lestari (Department of Physics Universitas Negeri Padang, 2024)
Twenty-first-century education requires students to possess several skills, one of which is creative thinking skills and student-centered learning, where teachers only act as facilitators to develop learning tools, one of which is teaching materials. This research aims to obtain an analysis of the need for the development of integrated STEM electronic teaching materials on alternative energy to enhance students' creative thinking skills. Data collection was carried out through teacher interview instruments, student characteristic questionnaires, and creative thinking skills test questions. Data were analyzed using descriptive statistical analysis techniques. The subjects of this study consist of one physics teacher and 30 students at SMAN 1 Payakumbuh District, as well as one physics teacher and 20 students at SMAN 1 Mungka District. Based on the data analysis conducted, three research findings were obtained. First, the constraints in the development of teaching materials and students' interest in electronic teaching materials in physics learning are categorized as very good with scores of 87.1 and 90.2, respectively. Second, the characteristics of students are categorized as good with a score of 73.5, and the characteristics of students consist of four aspects: students' interest in learning, students' attitudes, students' motivation to learn, and students' learning styles. Lastly, students' creative thinking skills are categorized as very poor with scores of 35.42 and 25.95. The research results indicate the need for a needs analysis for the development of integrated STEM alternative energy electronic learning materials to enhance students' creative thinking skills.